2020
DOI: 10.1097/nnr.0000000000000445
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and Acceptability of a Digitally Delivered Intervention for Parents of Very Low Birth Weight Infants

Abstract: Background Very low birth weight (VLBW) infants are at elevated risk for behavioral problems as early as the second year of life. The purpose of this feasibility study was to evaluate the adaptation and acceptability of an existing digitally delivered behavioral parent training program—the ezParent program, with the addition of weekly coaching calls—for parents of former VLBW infants in their second year of life. Objectives To assess the adaptation of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 30 publications
0
10
0
5
Order By: Relevance
“…Tips describe how parenting strategies can be modified to address neurodevelopmental delays common in VPT children. The tips are informed by findings from our feasibility study33 and literature of neurodevelopmental functioning, parental psychological distress and sensitive parenting in VPT children 40 41…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Tips describe how parenting strategies can be modified to address neurodevelopmental delays common in VPT children. The tips are informed by findings from our feasibility study33 and literature of neurodevelopmental functioning, parental psychological distress and sensitive parenting in VPT children 40 41…”
Section: Methods and Analysismentioning
confidence: 99%
“…Our previous research and the existing literature support the feasibility and efficacy of BPT and telephone coaching as individual treatment components for families of full-term children. [28][29][30][31][32][33] The Chicago Parent Programme (CPP) and its web-based application, the ezParent programme, is a BPT programme explicitly designed to be culturally responsive and sensitive for Black and Latinx families across a range of socioeconomic backgrounds and is effective in promoting prosocial child behaviour and improving parenting confidence and behaviour. 30 ezParent was designed to be self-directed to provide parent-controlled access as a feasible and potentially costeffective approach to address challenges in parent participation in face-to-face delivery.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Parenting interventions, specifically those targeting parent–child interaction patterns through the development of parenting skills such as differential attention, effective commands, and time‐out, have demonstrated high feasibility and acceptability (Luu, Xie, et al, 2017). Most parenting interventions for preterm children are targeted towards children ages 0–3 (Flierman et al, 2016; Greene et al, 2020; Rodríguez et al, 2014; Schappin et al, 2013). However, long‐term outcomes for early interventions suggest that effects may dissipate over time, with studies demonstrating no differences between the intervention and control group on behaviour problems at 1 (Schappin et al, 2013), 3 (Johnson et al, 2005) and 5 years following treatment (Johnson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Most parenting interventions for preterm children are targeted towards children ages 0-3 (Flierman et al, 2016;Greene et al, 2020;Rodríguez et al, 2014;Schappin et al, 2013). However, long-term outcomes for early interventions suggest that effects may dissipate over time, with studies demonstrating no differences between the intervention and control group on behaviour problems at 1 (Schappin et al, 2013), 3 (Johnson et al, 2005) and 5 years following treatment (Johnson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Various community-based programs reach Black women in Hillsborough County Florida (PGP: Growing and Glowing, n.d.). However, studies have also shown the potential to deliver pregnancy-related health information via digital sources, both prenatally and postnatally (Graham et al, 2019; Greene et al, 2020; Silfee et al, 2018). Further supporting the use of digital approaches, 40% of Black adults report getting health information online, and around 70% of Black adults use at least one social media platform (Lewis, 2017; Pew Research Center, 2019).…”
mentioning
confidence: 99%